HPV16-E7-Specific Activated CD8 T Cells in E7 Transgenic Skin and Skin Grafts - Jazayeri, Seyed Davoud; Kuo, Paula T.; Leggatt, Graham Robert; Frazer, Ian H. (Frontiers in Immunology, 2017)
Human Papillomavirus 16 E7 (E7) protein expression in skin promotes epithelial hyperproliferation and transformation to malignancy. Grafts of murine skin expressing E7 protein as a transgene in keratinocytes are not rejected from immunocompetent recipients, whereas grafts expressing ovalbumin, with or without co-expression of E7 protein, are promptly rejected, demonstrating that E7 associated non-antigen specific local immunosuppression is not a major determinant of lack of rejection of E7 transgenic skin. To determine whether failure of rejection of E7 skin grafts is due to failure to attract E7 specific effector T cells, E7-specific and ovalbumin specific effector CD8+ T cells, activated in vitro, were transferred to animals bearing E7 transgenic skin grafts. Three days after T cell transfer, E7 specific T cells were present in significantly greater numbers than OVA specific T cells in the grafted skin on animals bearing recently placed or healed E7 grafts, without graft rejection, and also in the ear skin of E7 transgenic animals, without obvious pathology. E7 and OVA specific T cells were present in lesser numbers in healed E7 grafts than in recently placed grafts, and in lesser numbers in recently placed E7 transgenic epidermal grafts without E7 associated hyperproliferation, derived from E7 transgenic mice with a mutated retinoblastoma gene. These data demonstrate that effector T cells are to some extent attracted to E7 transgenic skin specifically by E7 expression, but in large measure nonspecifically by the epithelial proliferation associated with E7 expression, and by the local inflammation produced by grafting. Failure of E7 graft rejection was observed despite trafficking of E7 specific effector T cells to E7 expressing epithelium, a finding of consequence for immunotherapy of HPV 16 E7 associated human cancers.